The Influence Of Perceived Value, Price Perception And Social Influence on Skincare Purchase Decisions - Alya Yanuar Putri; Nugroho, Dian Ari (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The beauty industry in Indonesia has shown significant growth, as recorded by BPOM RI, with the number of cosmetic companies increasing by 21.9% in 2023. The high growth rate of the cosmetics and skincare industry has triggered tight business competition. This research aims to analyze the effects of perceived value, price perception, and social influence on the decision of Natasha’s consumers in Malang to purchase the brand’s skincare products. The data of this quantitative research was harvested from questionnaires distributed to the brand’s 160 consumers. The data analysis includes validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. This study finds that perceived value, price perception, and social influence significantly affects the consumers’ decision to purchase the skincare products, that perceived value has the most dominant influence compared to other variables, and that price perception and social influence also contribute positively to the purchasing decision although their influences are not as strong as the influence of perceived value. These findings indicate that the value perceived by consumers plays an important role in determining their purchasing decisions.